Adolescence in the 21st century : constants and challenges - Spielhagen, Frances R., 1946-; Schwartz, Paul D. (Emerald Publishing Limited : Information Age Publishing, Inc., 2014)
What is wrong with young people today? This question has captured the concerns of the older generation about the habits and attitudes of the adolescents in their midst. The assumption is that there is indeed something wrong with young people. Even Plato must have rolled his eyes, as he relates his diatribe about the adolescents of Greece. Is the current generation of adolescents less motivated or less focused than their parents? How will they respond to the challenges facing them as they progress to adulthood? When, in fact, do they become adults? Although every generation draws upon their own unique and varied experiences, the speed of our current societal changes has created a very different adolescent passage for contemporary youth than ever before.The world as we know it has changed significantly and because of it, much of today's youth is decidedly different from their parents. Adolescence itself has shifted dramatically. Young children are displaying adolescent behaviors well before they are ready to act on or understand their meaning, and older adolescents are staying perpetual children. As one writer put it, "the conveyer belt that transported adolescents into adulthood has broken down". This book provides an interdisciplinary collection of research on the constants and challenges faced by young people today. Failure to launch? Social media? Economic stagnation? For the generation that is coming of age in a post-terrorist world and in the midst of economic upheaval, the challenges might seem insurmountable. However, in this book, scholars from across the academy, from sociology, psychology, education, philosophy, science, and business, explain how the young people today are responding to the constants of growth and change in adolescence and the unique challenges of life in the 21st century.